The Belt and Road Initiative the People's Republic of China's new assertive foreign policy - Mathias, Diego Santana (2019)
This thesis investigates the motivations and rationale underlying the People’s Republic of China’s (PRC) Belt and Road Initiative (BRI). It starts from a contextualisation of the project, scope and objectives, then presents an overview of the institutions and infrastructure created to promote, finance, and implement it, as well as of its main developments from 2013 to the present. In order to examine the key drivers for the BRI, it discusses the main (geo)political and (geo)economic challenges China faces after four decades of extraordinary economic growth following the politico-economic reforms and opening-up measures initiated by Deng Xiaoping, its accession to the World Trade Organisation (WTO), ‘Go Out’ policy, and recent economic slowdown. It argues China’s foreign policy has become more assertive since the 2008 international financial crisis, especially after Xi Jinping came into power, and that, in this context, the BRI besides being a response to China’s domestic needs and international challenges, it also fits its medium to long-term strategy to reshape the world order. The last part of the thesis delves into whether or not the BRI constitutes a strategy to materialise an alternative model of globalisation through soft power or a mechanism to expand China’s spheres of influence, as it is commonly suggested by the literature. It concludes that none of these arguments capture the logic of the BRI, as the strategy relies mostly on hard rather than soft power, and the concept of spheres of influence reflects a Western-centric view of the international system.